Longitudinal changes in clozapine dose in patients with treatment-resistant schizophrenia: a 5-year retrospective cohort study. (15th September 2022) - Tsukahara, Masaru; So, Ryuhei; Nakajima, Shinichiro; Kitagawa, Kohei; Kodama, Masafumi; Takeuchi, Hiroyoshi
Abstract : This retrospective cohort study aimed to investigate the longitudinal changes in clozapine dose over a 5-year period in patients with treatment-resistant schizophrenia (TRS). Patients with TRS who were administered clozapine at a hospital between April 2012 and December 2016 and continued treatment with clozapine for at least 1 year were included. Clozapine doses were compared at the dose-fixation point, defined as when the same regimen of clozapine had been continued for 8 weeks or longer, and the post-dose-fixation phase, at 12, 36 and 60 months after clozapine initiation. We included 103 patients and found no significant differences in clozapine dose between the dose-fixation point and post-dose-fixation phase. Approximately half of the patients were categorized into an unchanged group at 12 months after clozapine initiation, whereas approximately 40% of patients were categorized into either the decreased or increased group at 60 months. Multivariable regression analysis revealed that the change in clozapine dose between the dose-fixation point and 60 months after clozapine initiation was negatively associated with clozapine dose at the dose-fixation point. On average, the clozapine dose was unchanged during long-term treatment in patients with TRS, although the dose was decreased or increased in approximately 40% of the patients.